PENGARUH TAX AVOIDANCE, PROFITABILITAS, SALES GROWTH, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS LQ45 DI BEI PERIODE 2018-2020) - Devid Aprillando; Mujiyati Mujiyati (Accounting Global Journal, 2022)
The value of the company is defined as the selling price of the company's shares with the consideration of potential investors that the company is considered feasible, so that he is willing to make payments if the company's shares are sold in the capital market. The purpose of this study is to analyze whether there is an influence between tax avoidance, profitability, sales growth, leverage, and firm size on firm value in companies that are members of the LQ45 index listed on the IDX for the 2018-2020 period. The population in this study are all companies that are members of the LQ45 index listed on the BEI for the 2018-2020 period, totaling 201 companies. The sampling method used was purposive sampling method, so that 55 sample companies were obtained for three years of observation (2018-2020). The data analysis uses multiple linear regression analysis. Results of the study show that profitability, leverage, and firm size have an effect on firm value, while tax avoidance and sales growth have no effect. Keyword: Firm value, tax avoidance, profitability, sales growth, and leverage.